Hyperreactio Luteinalis (Multiple Luteinized Follicle Cysts): A Report of 10 Cases. (September 2021) - Watkins, Jaclyn C.; Lebok, Patrick; Young, Robert H.
Abstract : Hyperreactio luteinalis is a rare entity arising in pregnancy and in the setting of gestational trophoblastic diseases (ie choriocarcinoma, molar pregnancy) that presents with, typically, bilateral ovarian enlargement due to numerous follicle cysts. While the phenomenon is benign and spontaneously regresses following delivery or treatment, a specimen may be seen in pathology when oophorectomy or cystectomy is performed to exclude malignancy or to manage acute complications such as torsion. Such resections may exhibit overlapping microscopic features with cystic granulosa cell tumors. We thus reviewed 10 cases of hyperreactio luteinalis in the setting of pregnancy, the largest pathologic cohort to date, to highlight notable features of this disorder. Patients ranged from 22 to 30 yr old. Most patients (n=6) presented at time of cesarean section with incidentally discovered ovarian masses. Three patients presented in the postpartum period, and 1 underwent surgery at 28 wk gestation due to the finding of a unilateral ovarian mass. The ovaries ranged from 8.5 to 29 cm and were multicystic and bilateral in 8 of the cases. Histologic examination demonstrated multiple, variably sized cystic follicles lined by a granulosa cell layer of varying thickness and theca cells with marked eosinophilic cytoplasm. Stromal edema was often prominent, with theca cells occasionally noted in nests, cords, and as single cells in foci of edema. Mitoses were generally seen more often in the granulosa cell layer (mean=2.6 per high power fields) compared with the theca cell layer (mean=1 per 10 high power fields). This series documents the key features of hyperreactio luteinalis that differentiate it from the other benign mass forming lesions encountered in pregnancy, most notably large solitary follicle cyst of pregnancy and puerperium, as well as cystic granulosa cell tumors, especially the juvenile variant, which may also present during pregnancy. Of particular use in differentiating them from juvenile granulosa cell tumor is the absence of pale or vacuolated cytoplasm and solid growth of granulosa cells in cases of hyperreactio luteinalis.